Reconciled to Leisure: The Relationship Between Christianity, Leisure and Restorative Justice - Hannah Janzen; Paul Heintzman (Movement and Being: The Journal of the Christian Society for Kinesiology, Leisure and Sports Studies, 2024)
This paper seeks to explain the mutually reinforcing relationship between leisure and reconciliation from a Christian perspective. The paper begins by briefly defining the holistic approach to leisure from a Christian perspective, which will be the definition of leisure that is used throughout the paper. Christian teachings on reconciliation will then be outlined, both between the individual and God and between individuals. Restorative justice, the specific example of reconciliation that will be used in this paper, is defined as a process of justice that seeks to repair the harm that was caused through a crime.The paper then describes how leisure can be a tool for reconciliation. Contemplative leisure guides the individual in personal reflection which is necessary for reconciliation to others and spiritual reconciliation to Christ. Leisure also acts as a container to facilitate interpersonal reconciliation, as leisure activities are widely used in restorative justice programs to foster connection between offenders and members of the community. Leisure is also a product of reconciliation. As Christians restore their relationships with one another and with God, they are brought closer to the Kingdom of God and are able to experience the fullness of Christian leisure. On a physical level, offenders are given the resources necessary to live in leisure through reconciliation to society. Additionally, through the support of the community and the transformational power of God’s grace, reconciliation allows offenders, victims, and community members to deepen their spirituality and experience qualitative leisure through life in Christ. Both leisure and reconciliation are values of the Kingdom of God, and therefore are mutually reinforcing as a Christian is drawn into the fullness of life which Christ has to offer.
Keywords: Restorative Justice; Leisure; Incarceration; Reconciliation; Community; Christianity